À l’épreuve de l’affabulation en zone industrielle - Claire Dutrait (Itinéraires)
Éric Chauvier, in Somaland (2012), builds a story with documents explicitly derived from the fieldwork he conducted in the early 2000s in a SEVESO zone. Describing the complex textual apparatus that makes a catastrophe happen in language, and drawing on the pragmatist background of the anthropologist author, the analysis brings out the edifying dimension of what seemed to be only an ethnographic factography. Implementing certain language practices that still seem able to give substance to a relationship between the speaker, what he says and the person he is addressing in the tremor of catastrophe, the text engages the reader in a reflexive and sensitive experience that consists in recognizing a slow catastrophe and making sense to the traumatic word that emerges from it. Thus, Éric Chauvier's fable challenges everyone to notice their own potential involvement in the chronic catastrophe that characterizes our time, and helps to shed light on the conditions in which we can still give consistency to language, even fictionnal langage.